Extracellular vesicles released by cardiomyocytes in a doxorubicin-induced cardiac injury mouse model contain protein biomarkers of early cardiac injury - Chontida Yarana (2019)
© 2017 American Association for Cancer Research. Purpose: Cardiac injury is a major cause of death in cancer survivors, and biomarkers for it are detectable only after tissue injury has occurred. Extracellular vesicles (EV) remove toxic biomolecules from tissues and can be detected in the blood. Here, we evaluate the potential of using circulating EVs as early diagnostic markers for long-term cardiac injury. Experimental Design: Using a mouse model of doxorubicin (DOX)-induced cardiac injury, we quantified serum EVs, analyzed proteomes, measured oxidized protein levels in serum EVs released after DOX treatment, and investigated the alteration of EV content. Results: Treatment with DOX caused a significant increase in circulating EVs (DOX_EV) compared with saline-treated controls. DOX_EVs exhibited a higher level of 4-hydroxynonenal adducted proteins, a lipid peroxidation product linked to DOX-induced cardiotoxicity. Proteomic profiling of DOX_EVs revealed the distinctive presence of brain/heart, muscle, and liver isoforms of glycogen phosphorylase (GP), and their origins were verified to be heart, skeletal muscle, and liver, respectively. The presence of brain/heart GP (PYGB) in DOX_EVs correlated with a reduction of PYGB in heart, but not brain tissues. Manganese superoxide dismutase (MnSOD) overexpression, as well as pretreatment with cardioprotective agents and MnSOD mimetics, resulted in a reduction of EV-associated PYGB in mice treated with DOX. Kinetic studies indicated that EVs containing PYGB were released prior to the rise of cardiac troponin in the blood after DOX treatment, suggesting that PYGB is an early indicator of cardiac injury. Conclusions: EVs containing PYGB are an early and sensitive biomarker of cardiac injury.